2021
DOI: 10.1111/ajt.16746
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to SARS-CoV-2 is well preserved and symptom dependent in kidney transplant recipients

Abstract: Data on the immune response to SARS‐CoV‐2 in kidney transplant recipients are scarce. Thus, we conducted a single‐center observational study to assess the anti‐SARS‐CoV‐2 IgG seroprevalence in outpatient kidney transplant recipients (KTR; n = 1037) and healthcare workers (HCW; n = 512) during the second wave of the COVID‐19 pandemic in fall 2020 and evaluated the clinical variables affecting antibody levels. Antibodies against S1 and S2 subunit of SARS‐CoV‐2 were evaluated using immunochemiluminescent assay (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…Furthermore, we recently showed that KTRs mounted a similar level of anti-SARS-CoV-2 antibodies compared with healthcare workers as a result of natural immunization. 10 Using an identical antibody detection method in both studies, the observed SARS-CoV-2 antibody levels after a natural infection 10 were lower than in KTRs who were first infected with SARS-CoV-2 and later received a vaccine. Therefore, mRNA vaccines may serve as a booster of the immune response primed by natural immunization when immunosuppression is absent or reduced.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, we recently showed that KTRs mounted a similar level of anti-SARS-CoV-2 antibodies compared with healthcare workers as a result of natural immunization. 10 Using an identical antibody detection method in both studies, the observed SARS-CoV-2 antibody levels after a natural infection 10 were lower than in KTRs who were first infected with SARS-CoV-2 and later received a vaccine. Therefore, mRNA vaccines may serve as a booster of the immune response primed by natural immunization when immunosuppression is absent or reduced.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies, participants were screened for SARS-CoV-2 antibodies. However, even serological screening has its limitations, as varying proportions of SARS-CoV-2 positive KTRs will not mount antibodies 10,36 or the antibodies might decrease over time. Therefore, even individuals with negative SARS-CoV-2 antibodies might carry an immune memory and bias the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies concerning natural immunity after COVID-19 infection have been included. [ [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] ]…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the majority of SOT patients is able to mount a humoral response to SARS-COV-2. [ [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , 111 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation